Strategic risk management in water utilities: development of a holistic approach linking risks and futures - Linares Luis, Ana Margarida (Cranfield University, 2014)
Risk management plays a key role in water utilities. Although tools are well established at operational and tactical levels of management, existing methods at strategic level lack a holistic treatment and a long-term perspective. In fact, risks are analysed per se, despite being interconnected; and long-term scenarios are commonly used for strategic planning, rather than for risk management, most of the time being related to one single issue (for example: climate change). In order to overcome the limitations identified in the existing methodologies, a novel approach for water utilities to manage risk at strategic level was developed and tested in EPAL - the largest and oldest water utility in Portugal. It consists of (i) setting a baseline risks comparison founded on a systemic model developed ‗bottom-up‘ through the business; (ii) the construction of future scenarios and an observation of how baseline risks may change with time. Major contributions of this research are the linkage between operational and strategic risks, capturing the interdependencies between strategic risks; the ability to look at long term risk, allowing the visualizing of the way strategic risks may change under a possible future scenario; and the novel coupling of risks and futures research. For the water sector, this approach constitutes a useful tool for strategic planning, which may be presented to the Board of Directors in a simple and intuitive way, despite the solid foundations of the underlying analysis. It also builds on in-house expertise, promoting the dissemination and pervasiveness of risk management within the companies and, on the other hand, allowing unveiling of existing knowledge, making it explicit and more useful for the organization.
Keywords: Strategic risk management; futures; scenario building; water utilities; risk analysis; corporate management